2016
DOI: 10.1111/ppa.12614
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phenotypic diversity of Mediterranean populations of the olive knot pathogen, Pseudomonas savastanoi pv. savastanoi

Abstract: Pseudomonas savastanoi pv. savastanoi (Psav) is a member of P. syringae sensu lato, and causes olive knot disease, a disease first reported over 2000 years ago. Analysing 124 isolates of Psav from 15 countries by rep-PCR, the population genetic structure of Psav was investigated. A total of 113 distinct fingerprints were detected. Cluster analysis revealed the existence of two clusters and four subclusters. These clusters were associated with the geographic origin of isolates, which in turn correspond to histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…Asterisks indicate oleander strains included in pathovar Psv (see Figure 4). e Psv, Psn, Psf and Psr, P. savastanoi pathovars savastanoi, nerii, fraxini and retacarpa, respectively; + = presence, -= absence of a protein ortholog in the genomes of all strains included in the corresponding pathovar analyzed in this study Table 1. virulence variability (Penyalver et al, 2000;Moretti et al, 2017). Additionally, we show that symptom severity is not always correlated with population levels in planta.…”
Section: Correlation Between Phylogeny and Pathogenicitymentioning
confidence: 72%
See 1 more Smart Citation
“…Asterisks indicate oleander strains included in pathovar Psv (see Figure 4). e Psv, Psn, Psf and Psr, P. savastanoi pathovars savastanoi, nerii, fraxini and retacarpa, respectively; + = presence, -= absence of a protein ortholog in the genomes of all strains included in the corresponding pathovar analyzed in this study Table 1. virulence variability (Penyalver et al, 2000;Moretti et al, 2017). Additionally, we show that symptom severity is not always correlated with population levels in planta.…”
Section: Correlation Between Phylogeny and Pathogenicitymentioning
confidence: 72%
“…Nevertheless, some P. savastanoi populations show heterogeneous host ranges, which can even drastically differ between strains of the same pathovar (Cinelli et al, 2014;Morris et al, 2019). At the same time, and likely because of the reported lack of genetic diversity and overlapping host ranges, various genetic and phenotypical analyses did not establish a clear-cut differentiation among these pathovars (Janse, 1991;Sisto et al, 2007;Cinelli et al, 2014;Moretti et al, 2017). Thus, this well-established delineation of the host range, converts these four P. savastanoi pathovars of woody hosts in an excellent system to study the basis of host range in knot-and canker-forming bacterial pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…The typical knot of this disease is caused by phytohormones produced by the bacteria, which cause proliferation of cells surrounding the infection area. Olive knot is present mainly in Mediterranean countries, where climatic conditions often favor the spread of the disease (Moretti et al, 2017). During the research which was conducted in the spring of 2015, we found knot symptoms on trunk and branches of 4-year-old olive trees in the north of Iran.…”
Section: Resultsmentioning
confidence: 85%
“…All bacterial strains collected from the four areas of Malaysia were clustered together with the reference strains, indicating that the strains were genetically similar and share close phylogenetic relatedness with each other. This emphasizes that all our strains were likely originated and derived from a single emergence a long time ago [53]. Based on phylogenetic tree of the concatenated sequences of the four housekeeping genes (Fig 7), no major changes in the clustering pattern appeared since the position of the P. stewartii subsp.…”
Section: Plos Onementioning
confidence: 72%